Gastroesophageal reflux after per-oral endoscopic myotomy: Management literature - Tawheed, Ahmed; Bahcecioglu, Ibrahim Halil; Yalniz, Mehmet; El-Kassas, Mohamed (Baishideng Publishing Group Inc, 2024)
In this editorial, we respond to a review article by Nabi et al, in which the authors discussed gastroesophageal reflux (GER) following peroral endoscopic myotomy (POEM). POEM is presently the primary therapeutic option for achalasia, which is both safe and effective. A few adverse effects were documented after POEM, including GER. The diagnostic criteria were not clear enough because approximately 60% of patients have a long acid exposure time, while only 10% experience reflux symptoms. Multiple predictors of high disease incidence have been identified, including old age, female sex, obesity, and a baseline lower esophageal sphincter pressure of less than 45 mmHg. Some technical steps during the procedure, such as a lengthy or full-thickness myotomy, may further enhance the risk. Proton pump inhibitors are currently the first line of treatment. Emerging voices are increasingly advocating for the routine combining of POEM with an endoscopic fundoplication method, such as peroral endoscopic fundoplication or transoral incisionless fundoplication. However, more research is necessary to determine the safety and effectiveness of these procedures in the long term for patients who have undergone them.
Keywords: Achalasia; Per-oral endoscopic myotomy; Gastroesophageal reflux disease; Transoral incisionless fundoplication; Peroral endoscopic fundoplication